Regulatory role of the PKA pathway in dimorphism and mating in Yarrowia lipolytica - Cervantes Chávez, José A. (2009)
Previous studies on the dimorphic transition of Yarrowia lipolytica suggested opposite roles for MAPK and PKA pathways in this phenomenon. To obtain conclusive evidences for these opposite roles we isolated and disrupted the unique gene encoding the Pka catalytic subunit (TPK1). TPK1 was regulated only at the post-transcriptional level, with Pka activity increasing during yeast-like growth. tpk1 null mutants were viable and without growth defects, but more sensitive to different stress conditions. Δtpk1 mutants were mating-deficient, and grew constitutively in the mycelial form, whereas Δste11 (Mapkkk-less)/Δtpk1 double mutants grew in the yeast form, indicating that this is the default growth pattern of the fungus. Our data confirm that MAPK and PKA pathways operate in opposition during the dimorphic behavior of Y. lipolytica, but synergic in mating. These data stress the idea that in different fungi both signal transduction systems may operate distinctly or even be antagonistic or synergic in the coordination of cell responses to different stimuli. © 2009 Elsevier Inc. All rights reserved.